Estimation of self-sustained vibration for a finite element brake model based on the shooting method with a reduced basis approximation of initial conditions - Charroyer, L.; Chiello, O.; Sinou, J.-.J. (Journal of sound and vibration, 2020)
The objective of this paper is to discuss and propose an original nonlinear method for the estimation of nonlinear vibrations for mechanical systems subject to friction-induced noise and vibration. To fulfill such an objective the computation of nonlinear dynamic steady-state solutions of autonomous non-smooth contact systems prone to mono-instability is performed by developing an extension of the shooting method. This adaptation consists in using a reduced basis in the iterative process of this nonlinear method in order to seek the unknown initial conditions that verify condition of periodicity of the nonlinear solution of the problem. Efficiency of the proposed approach is illustrated through numerical examples for the prediction of self-sustained vibrations of a railway braking system.